Boosting Work Productivity: The Crucial Roles of Employee Engagement, Organizational Climate, and Ability - Asep Qustolani; Isrof Oktiasih (Studi Ilmu Manajemen dan Organisasi, 2026)
Purpose: The objective of this study is to examine the influence of employee engagement, organizational climate, and ability on work productivity among employees at PT Kaldu Sari Nabati Indonesia Research Methodology: This study uses a quantitative approach, combining descriptive and verification methods to test the hypotheses. Data were collected via questionnaires from 99 employees randomly sampled from a large population of 9,374. To ensure statistical accuracy, we used SPSS 25 to perform classical assumption tests and multiple linear regressions (t-tests and F-tests). Results: The results indicate that employee engagement, organizational climate, and ability have a positive and significant effect on work productivity. specifically, ability had the most dominant influence (28%), followed by employee engagement (22.8%) and organizational climate (21.6%). Conclusions: Increasing Employee Engagement, creating a conducive organizational climate, and improving employee ability significantly enhance work productivity at PT Kaldu Sari Nabati Indonesia. Limitations: This study offers a targeted exploration of the Majalengka Plant, prioritizing a deep dive into three pivotal performance drivers over a broad, multi-industry scope. While the findings are inherently localized to this facility, the study serves as a specialized benchmark for understanding workforce productivity within high-output manufacturing environments Contributions: This research enriches the Human Resource Management literature by providing rare empirical evidence on the specific drivers of productivity within the food manufacturing sector. Beyond its theoretical value, this study provides management with actionable, evidence-based insights to strategically optimize workforce performance in high-output industrial environments.